Ifá e Odus: interdisciplinaridade, lógica binária, e filosofia africana - Delfino, Jair (2020)
Within the studies of African and Afrodescendant history and culture, this Thesis makes an innovative insertion within the African tradition of the Ifá. The Ifá is a literary and philosophical body, which descends from a divinity between two worlds understood as the physical and the spiritual. Its objective is to systematize the representations of the Ifá, which work on questions of binary algebra and the organization of the meanings of the Ifá. The importance of this theme lies in examining, presenting and discussing specific knowledge of a culture and tradition that has as its educational process the orality and preservation of culture, and developing the interdisciplinary capacity and potentialities of memory, as well as inserting values and principles aimed at the religare of the human being with nature as a single body. We add to our proposal the concern with the systematic development of the learner; in this intention we present a discussion, we seek to be in accordance with Law nº. 10,639/03, contributing to it in the search for identity and belonging of the Afrodescendant people to the science behind the African philosophical, binary mathematics, memory, aesthetics, genealogical archetypes and interrelational and inter-personal interdisciplinarity of each, as potentialities to be developed. It uses as methodology qualitative research, carried out through literary revision and documental research. The results obtained are consolidated through binary methods of evaluation of the human being, an important complement for psycho-pedagogy of the predispositions of behavior of the human being; it also presents the dimension that reaches interdisciplinarity, by virtue of the cognition through memories, its consolidation and the devices that form important concepts in the consummation of apprehension and understanding by virtue of glimpsing the interdisciplinary formation of the educator and educator.